Mood versus energy/activity symptoms in bipolar disorder: which cluster of Hamilton Depression Rating Scale better distinguishes between mania, depression, and euthymia? - Cheniaux,Elie (2019)
Abstract Introduction Although bipolar disorder (BD) is traditionally included among mood disorders, some authors believe that changes in energy and motor activity, rather than mood changes, represent the true cardinal symptoms in mania and depression. The aim of the current study was to identify which cluster of the Hamilton Depression Rating Scale (HAM-D) better distinguishes between mania, depression and euthymia. Method A group of 106 patients with BD were followed for 13 years and repeatedly assessed with the HAM-D as well as with other clinical scales. To perform a comparison, HAM-D items were classified according to clinical criteria into three clusters: energy/activity symptoms, mood symptoms, and other symptoms. Item response theory (IRT) analyses were performed to provide a test information curve for those three clusters. We measured the prevalence of one cluster of symptoms over the other two throughout the latent trait. Results Considering HAM-D items individually, the IRT analysis revealed that there was a mixture of mood and energy/activity symptoms among the most discriminative items, both in depression and in euthymia. However, in mania, only energy/activity symptoms – i.e., general somatic symptoms and retardation – were among the most informative items. Considering the classification of items, both in depression as in mania, the energy/activity cluster was more informative than the mood cluster according to the IRT analysis. Conclusion Our data reinforce the view of hyperactivity and motor retardation as cardinal changes of mania and depression, respectively.